Det allmänna rättsmedvetandet och några svenska förarbeten på straffrättens område 2008-2018 - Andreas Anderberg (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article focuses on what is often termed the general (or public) sense of justice, GSJ for short. It illustrates the influence that the GSJ has had on various preparatory works in Swedish criminal law during a recent decade. It is often claimed that the GSJ is used as an argument in political discourse and decision making in the area of criminal law, especially to motivate criminalisation and harsher penal sanctions. Political points can be scored and general elections won by deploying a tough stance on crime. A problematic aspect is that by  appealing to the GSJ, legislators create a way to legitimise punitive measures with little or no empirical support in criminological research. Furthermore, the very concept of the GSJ is unclear, contentious, and characterised by a plethora of interpretations. This article provides background on the GSJ in the Nordic countries and thereby gives context to some recent legislative work in Sweden. The article concludes that legislators frequently reproduce phrases which, under closer inspection, appear quite hollow. The GSJ therefore seems to be more of a vague reference used for political purposes as opposed to a representation of actual popular values.